2020
DOI: 10.3389/fimmu.2020.00435
|View full text |Cite
|
Sign up to set email alerts
|

Egyptian Rousette IFN-ω Subtypes Elicit Distinct Antiviral Effects and Transcriptional Responses in Conspecific Cells

Abstract: Bats host a number of viruses that cause severe disease in humans without experiencing overt symptoms of disease themselves. While the mechanisms underlying this ability to avoid sickness are not known, deep sequencing studies of bat genomes have uncovered genetic adaptations that may have functional importance in the antiviral response of these animals. Egyptian rousette bats (Rousettus aegyptiacus) are the natural reservoir hosts of Marburg virus (MARV). In contrast to humans, these bats do not become sick w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…One suggested mechanism of greater disease resistance in bats is heightened innate immune response that is manifested in relatively high expression levels of type-I IFN or IFN-stimulated genes in bat cells and tissues 29,31,42,[81][82][83] . A recent study suggested that cells of Black Flying Fox (Pteropus alecto), a fruit bat from the Pteropodidae family (the same as Rousettus), show increased levels of the IRF transcription factors across bat tissues as well as higher basal expression of a set of IFN-stimulated genes 31 .…”
Section: Comparative Analysis Of Viral Rna-sensing Pathway Reveals Di...mentioning
confidence: 99%
See 1 more Smart Citation
“…One suggested mechanism of greater disease resistance in bats is heightened innate immune response that is manifested in relatively high expression levels of type-I IFN or IFN-stimulated genes in bat cells and tissues 29,31,42,[81][82][83] . A recent study suggested that cells of Black Flying Fox (Pteropus alecto), a fruit bat from the Pteropodidae family (the same as Rousettus), show increased levels of the IRF transcription factors across bat tissues as well as higher basal expression of a set of IFN-stimulated genes 31 .…”
Section: Comparative Analysis Of Viral Rna-sensing Pathway Reveals Di...mentioning
confidence: 99%
“…We focus on representatives of the major bat subordinal clades 40 -the Egyptian fruit bat, Rousettus aegyptiacus, and the insectivore bat Pipistrellus kuhlii (Kuhl's pipistrelle). Various aspects of Rousettus innate and adaptive immunity have been studied 13,[41][42][43][44][45][46] , due to its asymptomatic infection of filoviruses, as well as its association with infection with other viruses 47,48 . In contrast, antiviral immunity of Pipistrellus, a distantly related bat to Rousettus, remains poorly characterized, despite studies that suggested the presence of several Alpha-and Beta-coronaviruses (including closely related variants to MERS-CoV) in its population in Europe and the Middle East [49][50][51][52][53][54] .…”
Section: Introductionmentioning
confidence: 99%
“…Increased abundance of IRF1/3/7 and IFNs at steady state may be responsible for tissue-specific differences between bats and other mammals and/or for differential maturation of immune cell populations (Fig. 1) (120). Furthermore, differential metabolic activity in bats with decreases in reactive oxygen species may alter the potential for NF-B activation (121).…”
Section: Immunological Features Rendering Chiroptera a Reservoir For Pathogensmentioning
confidence: 99%
“…Indeed, a recent study compared two different IFNw subtypes from Rousettus aegyptiacus bats and found that IFNw9 displayed more effective antiviral activity against several RNA viruses in vitro compared to IFNw4 (130). Additionally, differences in expression and activity of porcine IFNw subtypes have also been demonstrated, with IFNw7 demonstrating the best antiviral activity in vitro (131).…”
Section: Ifnw Subtype Differencesmentioning
confidence: 99%
“…Just as there is growing appreciation that expanded IFNα subtypes provide an evolutionary advantage beyond redundancy, it stands to reason that the expansion of IFNω genes likewise imparts a fitness advantage for those species. Indeed, a recent study compared two different IFNω subtypes from Rousettus aegyptiacus bats and found that IFNω9 displayed more effective antiviral activity against several RNA viruses in vitro compared to IFNω4 ( 130 ). Additionally, differences in expression and activity of porcine IFNω subtypes have also been demonstrated, with IFNω7 demonstrating the best antiviral activity in vitro ( 131 ).…”
Section: Infectious Diseasesmentioning
confidence: 99%